STRATEGI PENGEMBANGAN KARIR DAN BUDAYA ORGANISASI - Hardiyana, Aan (Majalah Bisnis & IPTEK, 2021)
Psychological success is the highest goal of a person’s career, namely feeling proud of one’s accomplishments were obtained when the most important goal in life is achieved. Initial promotion is important in shaping the organization. Based on a survey of some of the CEOs, the company is based on the promotion of social presentability, visibility, domain or organizational skills policial. Such evidence indicates that management skills can bind individual career success. Organizational career management covers a range of policy and organizational measures to improve the effectiveness of their work career. Definition of organizational career refers to the employee structure and practices that provide guidance on how to hires, develop and give tasks to employees. Keywords: career development; organizational culture